The Core of the English Lexicon: Stress and Graphophonology - Véronique Abasq; Quentin Dabouis; Jean-Michel Fournier; Isabelle Girard (Anglophonia)
This paper is a study of the 5000 most frequent word-forms of the English lexicon. Both stress and graphophonological regularities are evaluated within Fournier’s (2010b) framework. The results show the high efficiency of Fournier’s model and that a large number of exceptions fall into well-known classes.